Reappraisal of statin primary prevention trials: implications for identification of the statin-eligible primary prevention patient - Mancini, G B John; Ryomoto, Arnold; Yeoh, Eunice; Iatan, Iulia; Brunham, Liam R; Hegele, Robert A (European journal of preventive cardiology, 2025)
Identification of patients eligible for primary prevention statin therapy is complex, often relying upon risk algorithms that diverge internationally. Our goal was to develop a simpler global definition of statin-eligible primary prevention patients. Randomized clinical trials (RCTs) cited in North American and European dyslipidemia guidelines justifying primary prevention statins for cardiovascular risk reduction were critically reappraised according to eligibility criteria and characteristics of actual enrollees. Statin-eligibility based on meeting minimal enrolment criteria versus risks calculated using either the Framingham Risk Score, the Pooled Cohort Equation and the Systematic Coronary Risk Estimate 2 were contrasted. Patient scenarios meeting minimal RCT eligibility criteria seldom attained high enough 10 year risk of events according to the algorithms tested and thus would not be eligible for statin therapy. Overall, enrollees were 63.9 ± 8.9 years (mean ± SD) with low density lipoprotein-cholesterol (LDL-C) 3.53 ± 0.91 mmol/L. Enrollees in trials studying the lowest LDL-C levels were generally older and had additional risk factors. Results of primary prevention RCTs justify treatment of more subjects and lower risk subjects than current risk algorithm-based guidelines. Based on a synthesis of RCT inclusion/exclusion criteria and the characteristics of enrollees, we propose that a statin-indicated primary prevention subject is one who is 40 to 70 years with a low density lipoprotein-cholesterol (LDL-C) ≥ 3.0 mmol/L or is 55 to 80 years with LDL-C ≥ 1.8 mmol/L and additional risk factors.